STUDY EFFECT OF MICROBIAL INOCULANTS ON DECOMPOSITION OF BARLEY STRAW - Irina RUSAKOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of the study was to analyze the effect of microbial inoculants on the decomposition of barley straw. The field experiment, located at the soddy-podzolic sandy loam soil in order to study the effect of microbiological preparations on biotransformation of barley straw, biological properties of soddy-podzolic soil. The conclusion was that the use of microbiological agents-destructors is justified firstly when incorporation of high doses of straw in the cereal crop rotations, use of straw under cereal culture, in technology no-till, i.e. in the situations when it is necessary to provide conditions for the speedy decomposition of post-harvest crop residues, used as a fertilizer, in order to prevent its negative impact and to promote positive action.